Cheshm ‘eye’ Expressions in Persian: A Different Perspective - Muhammad Salehi (LET: Linguistics, Literature and English Teaching Journal, 2022)
This study seeks to explore the conceptualization of the word Cheshm ‘eye’ which constructs a vast part of spoken discourse in Persian expressions. Taking a close look at a number of modern Persian expressions in Iranian culture, containing the body-part term Cheshm, one can easily become aware of lack of a definite pattern in those expressions. Given that this shortage makes a lot of misunderstandings among non-native speakers, the present exploration is done as a kind of a qualitative research which is based on a library-oriented study as well as general and theoretical scholarship that aims to bridge the gap by categorizing the conceptualization of the word Cheshm ‘eye’ under the classification of desire and ambition, vice versus virtue, hope and expectation, affection versus aversion as well as vision and outlook. After the introduction of Persian expressions and the context in which they are used, the assumed cultural factors which are thought to have motivated such conceptualizations are discussed. It is hoped that the study at hand aids anyone learning Persian as a second/foreign language in order to better understand the expressions and also shed enough light on some of the major aspects of conceptualization of the body-part term Cheshm ‘eye’ in Persian language.